RESEARCH OF CHARACTERISTICS OF WEIGHTS - ANALYZERS WITH THREE-DIMENSIONAL MONOPOLAR HF FIELDS WITH SQUARE-LAW DISTRIBUTION OF POTENTIAL - Hizirova, M.A.; Аhmediyarova, А.Т.; Kasimova, D.Т.; Nurtaeva, G.К. (Recent Contributions to Physics, 2018)
Experimental mass analyzers from two are investigated and three-dimensional linear monopolar high-frequency fields, define their analytical possibilities and consumer characteristics.